The Impact of COVID-19 on Radiological Science Students and Interns at King Saud bin Abdulaziz University for Health Sciences: Cross-Sectional Study - Kaifi R; Subahi A; Alqarni S; Jaddawi A; Alghamdi A; Alshamrani KM (Advances in Medical Education and Practice, 2023)
Reham Kaifi,1– 3 Ahmed Subahi,2,4 Salem Alqarni,1 Ahmed Jaddawi,1 Ahmed Alghamdi,1 Khalid M Alshamrani1– 3 1Department of Radiological Sciences, College of Applied Medical Sciences, King Saud bin Abdulaziz University for Health Sciences, Jeddah City, Saudi Arabia; 2King Abdullah International Medical Research Center, Jeddah City, Saudi Arabia; 3Medical Imaging Department, Ministry of the National Guard - Health Affairs, Jeddah City, Saudi Arabia; 4Department of Basic Sciences, College of Science and Health Professions, King Saud bin Abdulaziz University for Health Sciences, National Guard, Jeddah City, Saudi ArabiaCorrespondence: Reham Kaifi, Email kaifir@ksau-hs.edu.saIntroduction: The impact of the coronavirus disease (COVID-19) outbreak on many parts of our lives cannot be overstated. This study aimed to identify the psychological, physical activity, and educational effects of COVID-19 on radiological sciences students and interns at the three campuses of King Saud bin Abdulaziz University for Health Sciences (KSAU-HS), Riyadh, Jeddah, and Alahsa.Methods: A cross-sectional study was conducted between November and December 2021 among Saudi-108 radiological sciences students and interns using non-probability convenient sampling at King Saud bin Abdul-Aziz University for Health Science (KSAU-HS), Riyadh, Jeddah, and Alahsa using a validated questionnaire. Statistical analyses were conducted using Excel and JMP statistical software.Results: 102 out of 108 completed the questionnaire resulting in a 94.44% response rate. The percentage of the overall negative psychological impact was 62%. For the physical activity effects of COVID-19 among students and interns, 96% reported a decline in their physical activities. 77% of participants reported a fair impression that the students were able to achieve some of their academic goals and acquired new skills during the pandemic, and 20% reported a good impression. They achieved all their goals and developed new skills, whereas 3% reported bad impressions and needed to achieve their goals or improve their skills.Conclusion: COVID-19 had a negative psychological and physical activity impact on RADs students and interns at the three KSAU-HS campuses in the Kingdom of Saudi Arabia. Despite technical difficulties, students and interns reported positive academic outcomes from COVID-19.Keywords: COVID-19, radiological sciences students, interns, psychological effect, clinical skills, radiography education